Numerical modelling of stiffness and strength behaviour of top-seat flange-cleat connection for cold-formed double channel section - Lee, Yeonghuei (2013)
Prediction of structural behaviour by numerical modelling can reduce the cost in conducting full-scaled experiments. This paper studies the stiffness and strength behaviour of topseat flange-cleat connection for cold-formed steel double channel sections using finite element method. In this investigation, cold-formed channel sections are assembled back-to-back to form Ishape beam and column members. The 2 mm cold-formed bracket and 6 mm hot-rolled angle are used to connect the members. The results were collected from different beam depth ranged 150 mm, 200 mm and 250 mm. The rotational stiffness and strength obtained from the numerical modelling are then compared to the design requirements from BS EN 1993-1-8 and experimental data. The comparison of moment-rotation behaviour for top-seat flange-cleat connection has shown not more than 35% difference for strength behaviour and 50% difference for rotational stiffness behaviour between numerical modelling and experimental data. However, there is a noticeable difference between finite element models and analytical calculation. The differences are recorded from 18% to 65% for strength behaviour and between 1% and 153% for stiffness behaviour. The differences obtained between finite element analysis and experimental investigation are caused by edge stiffener while differences from finite element models and analytical models are due to strain hardening. © (2013) Trans Tech Publications, Switzerland.